Optimizing Human Resource Management Strategy in Improving Food Security Programs - Verdian, Refi; Rahayu, Heffi Christya; Afrizal, Andi (Strata Social and Humanities Studies, 2025)
This study investigates optimizing human resource management (HRM) strategies to strengthen food security programs through localized institutional efforts, focusing on the Village-Owned Enterprise (BUMDes) Sumber Rezeki in Kota Raya Village, Rokan Hulu Regency. Despite Indonesia's abundant natural resources, rural areas face systemic socio-economic challenges that hinder food security initiatives. This research applies a qualitative descriptive approach, utilizing in-depth interviews, direct observations, and document analysis. Internal and external factor evaluations were conducted using IFAS and EFAS matrices and a SWOT analysis to identify strategic priorities. Results indicate that BUMDes Sumber Rezeki holds moderate internal strength (IFAS score: 2.78) and faces a balanced external environment (EFAS score: 2.78), positioning it within the Growth Strategy quadrant. Key strengths include funding capacity, community engagement, and access to training. Strategic recommendations involve intensifying HR development, enhancing administrative systems, and fostering transparent governance to leverage external collaborations. Addressing internal weaknesses and mitigating external threats such as climate change and limited budgets is essential for building a resilient and sustainable rural food security model. The findings contribute to the discourse on micro-institutional HRM strategies and their role in advancing food security in developing contexts.